Mengoptimalkan Penjualan Online Melalui Teknik Data Mining (Studi Kasus E-Commerce) - Apriana, Diwi; Yuliansyah, Chandra (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The aim of this research is to optimize online sales through data mining techniques (e-commerce case study). This type of research is a literature review. Data collection with documentation. Data analysis with SLR. Research result. Research results The use of data mining techniques in optimizing online sales, especially in the context of e-commerce, can provide significant benefits for companies. By analyzing purchasing patterns and consumer behavior using data mining algorithms, companies can identify customer trends and preferences, improve promotional targeting, and optimize marketing strategies. This not only improves operational efficiency, but also results in a significant increase in sales. Thus, the integration of data mining techniques becomes a necessity for e-commerce companies that want to remain competitive and successful in an increasingly competitive market